DICLOFENAC-INDUCEDURTICARIA IN PAEDIATRIC PATIENT - C, Deepalatha; Prasad, Raja Vikram; CHANDRA, SATISH; Mohan, P. Murali; Lakshmi., Vijaya (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Non-steriodal anti-inflamatory drugs are most commonly used analgesics. Rash, itching, angioedma, gastritis are common reactions that we see with these drugs. A 13-year old boy presented with skin rash, eruptions on both eyes on forehead when Diclofenac was administered in the dose of 50mg (Reactin) which was diagnosed as urticarial angioedema. The case highlights the potential danger of using Reactin in hypersensitive individuals.